An exploratory study of group Adverse Impact in a recruitment and selection strategy - R. J. Snelgar (South African Journal of Economic and Management Sciences, 2003)
The Adverse Impact model was developed by the judicial system of the United States of America and the United Kingdom as a practical method to make legal judgements to determine whether designated groups are being unfairly discriminated against at any stage of an assessment process. The model has been used to assess various recruitment and selection instruments and measures. This study has been groundbreaking in that the application of the Adverse Impact model within the South African employment scenario is relatively new. An exploratory research design was used to analyse Adverse Impact at each stage of a recruitment and selection strategy. The model was applied to assess whether the instruments used, had an adverse impact on any of the designated groups.